2009
DOI: 10.1093/cvr/cvp003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac chymase converts rat proAngiotensin-12 (PA12) to angiotensin II: effects of PA12 upon cardiac haemodynamics

Abstract: PA12 may act as a circulating substrate for cardiac chymase-mediated AngII production, in contrast to ACE-mediated AngII production from AngI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…ACE has been reported to be involved in the conversion of ANG-(1-12) to ANG II in some regions of the brain (e.g., the NTS) (1). Chymase has been reported to be one of the alternate pathways by which ANG II is formed in various tissues (37). In the central nervous system, this pathway is involved in ANG II formation in the pituitary stalk and pineal gland (2).…”
Section: Discussionmentioning
confidence: 99%
“…ACE has been reported to be involved in the conversion of ANG-(1-12) to ANG II in some regions of the brain (e.g., the NTS) (1). Chymase has been reported to be one of the alternate pathways by which ANG II is formed in various tissues (37). In the central nervous system, this pathway is involved in ANG II formation in the pituitary stalk and pineal gland (2).…”
Section: Discussionmentioning
confidence: 99%
“…The vasoconstrictor and pressor effects of proang-12 are abolished by ACE inhibitors and angiotensin receptor blockers, which suggests ACE is involved in the conversion of proang-12 to Ang II. [8][9][10] However, Prosser et al 11,12 reported that chymase inhibition attenuates proang-12-induced cardiac damage caused by ischemia-reperfusion in rat hearts ex vivo, as well as proang-12-induced constriction of isolated rat arteries. This suggests that chymase is also involved in the conversion of proang-12 to Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…Ang-(1-12) added to the isolated rat heart resulted in increased Ang II production, coronary vasoconstriction, and impaired recovery from ischemia-reperfusion injury. 112 Although the enzymatic mechanism responsible for cardiac Ang-(1-12) formation from angiotensinogen remains an open question, a recent study suggested a chymase-mediated mechanism in the ischemia-reperfusion rat heart. 112 In keeping with these observations, studies from Ferrario's 113 laboratory showed that although both ACE and chymase form Ang II from Ang-(1-12), the latter assumed an even greater role for Ang II formation in spontaneously hypertensive rats.…”
Section: Ang-(1-7) and Ace2 And Other Angiotensin Peptides In The Heartmentioning
confidence: 99%
“…112 Although the enzymatic mechanism responsible for cardiac Ang-(1-12) formation from angiotensinogen remains an open question, a recent study suggested a chymase-mediated mechanism in the ischemia-reperfusion rat heart. 112 In keeping with these observations, studies from Ferrario's 113 laboratory showed that although both ACE and chymase form Ang II from Ang-(1-12), the latter assumed an even greater role for Ang II formation in spontaneously hypertensive rats. In summary, Ang-(1-12) is clearly present in the heart and represents an alternate substrate contributing to formation of Ang peptides by a nonrenin-dependent mechanism.…”
Section: Ang-(1-7) and Ace2 And Other Angiotensin Peptides In The Heartmentioning
confidence: 99%
See 1 more Smart Citation